<h3>
Answer with Step-by-step explanation:</h3>
1. 2(h - 8) - h = h - 16
Using distributive property
2h-16-h=h-16
i.e. h-16=h-16
Hence, this equation is true for any value of h
2. 4(x - 3) + 5 = 1
Using distributive property
4x-12+5=1
i.e. 4x-7=1
i.e. 4x=8
i.e. x=2
3. 70 = -7(-2 -2z)
Using distributive property
70= 14+14z
or 14z=70-14
i.e. 14z= 56
i.e. z= 4
4. -2x + 4 = 2(4x-3)-3(-8+4x)
Using distributive property
-2x+4= 8x-6+24-12x
Taking x on one side and constant terms on other
12x-8x-2x
5. u + 2 =4
on subtracting both side of the equation by 2 we have:
i.e. using subtraction property of equality:
u=4-2
i.e.
u=2